Integration of mesoporous bioactive glass nanoparticles and curcumin into PHBV microspheres as biocompatible composite for drug delivery applications - Aguilar Rabiela, Arturo Elias; Leal-Egaña, Aldo; Nawaz, Qaisar; Boccaccini, Aldo R. (Molecules, 2021)
Bioactive glasses (BGs) are being increasingly considered for biomedical applications. One convenient approach to utilize BGs in tissue engineering and drug delivery involves their combination with organic biomaterials in order to form composites with enhanced biocompatibility and biodegradability. In this work, mesoporous bioactive glass nanoparticles (MBGN) have been merged with polyhydroxyalkanoate microspheres with the purpose to develop drug carriers. The composite carriers (microspheres) were loaded with curcumin as a model drug. The toxicity and delivery rate of composite microspheres were tested in vitro, reaching a curcumin loading efficiency of over 90% and an improving of biocompatibility of different concentrations of MBGN due to its administrations through the composite. The composite microspheres were tested in terms of controlled release, biocompatibility and bioactivity. Our results demonstrate that the composite microspheres can be potentially used in biomedicine due to their dual effects: bioactivity (due to the presence of MBGN) and curcumin release capability.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Bioactive glass nanoparticles; Composite microspheres; Drug delivery systems; PHBV